How do the joint effects of aspiration and social influence promote cooperation in the prisoner’s dilemma game? - Liu, Chao; Wang, Hexin; Dai, Yu (Frontiers in Physics, 2023)
Various mechanisms have been proposed to promote cooperation in evolutionary games, including aspiration and social influence. However, the joint effects of aspiration and social influence have so far been ignored in the literature. Thus, we discuss the joint effects of aspiration and social influence on promoting cooperation and how the level of cooperation changes in four heterogeneous microenvironments composed of different aspirations and social influences in the Prisoner's Dilemma Game (PDG). Simulation results show that aspiration and social influence mechanisms are jointly effective at improving cooperation in the PDG. More precisely, the aspiration mechanism promotes cooperation unconditionally, but that the social influence mechanism promotes it conditionally.